EXAMINING THE RELATIONSHIP BETWEEN FARM INVESTMENT SUPPORT AND AGRICULTURAL AREA, PRODUCTION AND PRODUCTIVITY IN TELANGANA, INDIA - S. Siva Prasad; Reddy, K. Anji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research investigates the correlation between farm investment assistance provided by Rythu Bandhu and essential agricultural performance metrics, specifically the area cultivated, production levels, productivity, and agriculture's economic contribution to the state. The analysis utilizes secondary data obtained from the Directorate of Economics and Statistics, Government of Telangana, the Ministry of Agriculture, and the Socio-Economic Outlook of Telangana, encompassing the period from 2018–19 to 2023–24. The study utilizes descriptive statistics and Karl Pearson’s correlation analysis to examine the strength and direction of associations among variables such as the number of scheme beneficiaries, total farm investment under Rythu Bandhu, total area covered, and economic indicators, including the contribution of agriculture to GSDP and per capita income. The results show a strong and statistically significant positive relationship between the number of beneficiaries and both the total financial support (r = 0.938, p = 0.006) and the area covered by the program (r = 0.885, p = 0.019). This means that more outreach and investment are closely linked. Additionally, the number of beneficiaries is significantly correlated with agriculture's contribution to GSDP (r = 0.817, p = 0.047), indicating a favorable macroeconomic effect of the scheme. But the links between Rythu Bandhu variables and bigger indicators like the share of agriculture in Gross State Value Added (GSVA) and per capita income are not statistically significant, even though, they are positive. This shows that there may be a gap between growth in specific sectors and their relative contribution to the overall state economy. This could be because non-agricultural sectors are growing faster. In conclusion, the study offers empirical evidence that Rythu Bandhu has favorably impacted agricultural investment and economic output, especially regarding the enhancement of coverage and the augmentation of farm-level support. Its broader effects on structural economic indicators, on the other hand, are still limited. This suggests that we need to use integrated strategies that combine direct support with long-term infrastructure, extension, and market linkages.